[Ge5Ni2(CO)3]2−: the first functionalized cluster of closo-[Ge5]2−. Issue 47 (30th May 2017) - Liu, Chao; Li, Lei-Jiao; Pan, Qing-Jiang; Sun, Zhong-Ming
Abstract : A functionalized cluster derivative of closo -[Ge5 ] 2− has been prepared and structurally characterized for the first time. Abstract : A new functionalized cluster, [Ge5 Ni2 (CO)3 ] 2−, derived from the closo -[E5 ] 2− (E = Si–Pb) anions which have been known for decades but whose reactivity has rarely been studied, was successfully isolated from the reaction of [Ni(PPh3 )2 (CO)2 ] and [Ge5 ] 2− in ethylenediamine (en) solution, and its formation pathway was also investigated.